Coal-based solid waste-based ultrahigh water filling material and preparation method thereof

By using coal-based solid waste-based ultra-high water filling materials with specific ratios, the problems of insufficient utilization, stability and environmental adaptability of traditional materials in coal-based solid waste treatment are solved, and material cost reduction and performance improvement are achieved.

CN119751004AActive Publication Date: 2025-04-04CCTEG COAL MINING RES INST

Patent Information

Application Number
CN202411711057.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-04
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

When dealing with coal-based solid waste, traditional ultra-high water filling materials have problems such as low solid waste utilization rate, insufficient material stability and strength, poor environmental adaptability, and the process has problems such as high energy consumption, high preparation cost, and complex construction.

Method used

The coal-based solid waste-based ultra-high water filling material consisting of sulfaluminate clinker, citric acid, iron ethylenediaminetetramethylphosphonate, desulfurization gypsum, fly ash, aluminum sulfate, N-(2-nitrophenyl)ethanolamine and triisopropoxy titanium chloride complex was prepared through specific ratios and treatment processes.

Benefits of technology

It improves the utilization rate of coal-based solid waste, reduces material costs, enhances the stability and strength of materials, and improves environmental adaptability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751004A_ABST
    Figure CN119751004A_ABST
Patent Text Reader

Abstract

The invention discloses a coal-based solid waste-based ultrahigh water filling material and a preparation method thereof. The filling material can improve the utilization rate of coal-based solid wastes, reduce the material cost, improve the stability and strength of the material and enhance the environmental adaptability. The filling material is composed of a component A and a component B. The component A comprises the following components: sulphoaluminate clinker, citric acid and ethylenediamine tetra (methylene phosphonic acid) iron; the component B is prepared from the following components: desulfurized gypsum, fly ash, aluminum sulfate, N-(2-nitrophenyl) ethanolamine and a triisopropoxy titanium chloride complex.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of special mining filling materials, and in particular to a coal-based solid waste-based ultra-high water filling material and a preparation method thereof. Background Art

[0002] Ultra-high water filling material (also called ultra-high water cementing filling material) is a new type of coal mine filling material, which is characterized by that in the formed consolidated body, the volume of water accounts for more than 90%, while the volume of the material itself accounts for less than 10%. This material is usually made of bauxite and gypsum as the main raw materials, through a specific ratio and processing process. Ultra-high water filling material is mainly used for filling mining in coal mines, especially in the large-scale filling mining of "three-down" compressed coal. In addition, ultra-high water filling material is also used in the fields of pre-filling empty tunnel mining, fire prevention, leaving tunnels along the empty tunnels, ground fissure management, aquifer grouting transformation, etc.

[0003] In terms of treating coal-based solid waste, traditional ultra-high water filling materials have some problems, such as low solid waste utilization rate, insufficient material stability and strength, poor environmental adaptability, etc. In addition, traditional processes may have problems such as high energy consumption, high preparation cost, and complex construction. Summary of the invention

[0004] The embodiment of the present application provides a coal-based solid waste-based ultra-high water filling material and a preparation method thereof. The filling material can improve the utilization rate of coal-based solid waste, reduce material costs, and at the same time improve the stability and strength of the material and enhance environmental adaptability.

[0005] The present invention provides a coal-based solid waste-based ultra-high water filling material, which consists of a component A and a component B, wherein the component A includes the following components: sulphoaluminate clinker, citric acid and ethylenediaminetetra(methylenephosphonic acid) iron; the component B includes the following components: desulfurized gypsum, fly ash, aluminum sulfate, N-(2-nitrophenyl)ethanolamine and triisopropoxytitanium chloride complex.

[0006] In some embodiments, the components in the component A include, by mass, 100 parts of sulphoaluminate clinker, 0.2-0.4 parts of citric acid, and 0.01-0.02 parts of ethylenediaminetetramethylenephosphonic acid iron.

[0007] In some embodiments, the components in the component B include, by mass, 40-60 parts of desulfurized gypsum, 35-50 parts of fly ash, 5-10 parts of aluminum sulfate, 0.1-2 parts of N-(2-nitrophenyl)ethanolamine and 0.02-0.1 parts of triisopropoxytitanium chloride complex.

[0008] The present invention also provides a method for preparing a coal-based solid waste-based ultra-high water filling material, comprising:

[0009] Mixing component A with water to form a first mixed slurry;

[0010] Mixing component B with water to form a second mixed slurry;

[0011] The first mixed slurry and the second mixed slurry are mixed to form a coal-based solid waste-based ultra-high water filling material.

[0012] In some embodiments, component A is mixed with water in a mass ratio of 1:(5-7) to form a first mixed slurry.

[0013] In some embodiments, component B is mixed with water in a mass ratio of 1:(5-7) to form a second mixed slurry.

[0014] In some embodiments, the first mixed slurry and the second mixed slurry are mixed in a mass ratio of 1:(0.5-2) to form a coal-based solid waste-based ultra-high water filling material.

[0015] The present invention provides a coal-based solid waste-based ultra-high water filling material and a preparation method thereof. The filling material can improve the utilization rate of coal-based solid waste, reduce material costs, and at the same time improve the stability and strength of the material and enhance environmental adaptability. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A flow chart of a method for preparing a coal-based solid waste-based ultra-high water filling material provided according to some embodiments is exemplified. DETAILED DESCRIPTION

[0017] In order to better understand the above technical solution, the technical solution of the present application is described in detail below through specific implementation methods.

[0018] In order to solve the above technical problems, an embodiment of the present application provides a coal-based solid waste-based ultra-high water filling material, which can improve the utilization rate of coal-based solid waste, reduce material costs, and at the same time improve the stability and strength of the material and enhance environmental adaptability.

[0019] The filling material consists of component A and component B, wherein the component A includes the following components: sulphoaluminate clinker, citric acid and ethylenediaminetetra(methylenephosphonic acid) iron; the component B includes the following components: desulfurized gypsum, fly ash, aluminum sulfate, N-(2-nitrophenyl)ethanolamine and triisopropoxytitanium chloride complex.

[0020] In the embodiment of the present application, sulphoaluminate clinker is the main component of component A, which plays the role of hydration to form ettringite skeleton. Citric acid is a retarder, which mainly delays the hydration of sulphoaluminate clinker, so that component A meets the time requirements specified in DB13T 1660-2012 mining ultra-high water material standard.

[0021] Ethylenediaminetetra(methylenephosphonic acid)ferric plays the role of reinforcing agent and suspending agent. Ethylenediaminetetra(methylenephosphonic acid)ferric is a macromolecule that can be suspended in component A to increase the skeleton of the slurry. At the same time, the amino group in the molecule can promote the dissolution and hydration of sulphoaluminate clinker, and increase the strength of high-water filling materials in the later stage.

[0022] Desulfurized gypsum and fly ash are the main components of component B. Desulfurized gypsum mainly provides calcium ions and sulfate ions, and fly ash mainly provides hydroxide ions and calcium ions, providing the source of calcium ions, hydroxide ions and sulfate ions for the formation of ettringite. The formation formula of ettringite is as follows:

[0023] C4A3$(sulfoaluminate clinker)+8C$·2H(desulfurized gypsum)+6CH(calcium hydroxide, provided by fly ash)+74H→3C6A$3H32(ettringite).

[0024] Aluminum sulfate is a coagulant that serves the purpose of generating trace amounts of ettringite with calcium oxide in fly ash. The specific formula is as follows: 4CaO+32H2O+Al2(SO4)3=3C6A$3H32(AFt). The trace amounts of ettringite generated here can be used as crystal seeds. When component A and component B are mixed, the filling material can solidify quickly, thereby meeting the setting time requirements after mixing in the standard.

[0025] N-(2-nitrophenyl)ethanolamine is a suspending agent and catalyst. Because the ultra-high water filling material has a high water content, it is easy to bleed water after mixing. After adding N-(2-nitrophenyl)ethanolamine, when component A and component B are mixed, N-(2-nitrophenyl)ethanolamine and ethylenediaminetetra(methylenephosphonic acid) iron both contain amino groups, which can form hydrogen bonds with the crystal water in the calcium sulfoxide, linking each other to form a three-dimensional network structure, reducing water bleeding and skeleton porosity, and improving the stability and strength of the filling material.

[0026] The titanium ions in the triisopropoxy titanium chloride complex have empty electron orbits, and can form coordination bonds with atoms with lone pairs of electrons in the N-(2-nitrophenyl)ethanolamine molecule to enhance the chemical activity of the substance. When mixed with component A, the activated N-(2-nitrophenyl)ethanolamine and ethylenediaminetetra(methylenephosphonic acid) iron coexist, and interact with the iron ions or ethylenediaminetetra(methylenephosphonic acid) molecules therein, further enhancing the complexing and lap-bonding ability of the entire system. At the same time, the titanium ions interact with substances such as sulphoaluminate clinker, desulfurized gypsum or calcium hydroxide, promoting the reaction and accelerating the formation rate of ettringite.

[0027] In some embodiments, the components in the component A include, by mass, 100 parts of sulphoaluminate clinker, 0.2-0.4 parts of citric acid, and 0.01-0.02 parts of ethylenediaminetetramethylenephosphonic acid iron.

[0028] In the embodiment of the present application, if the citric acid exceeds 0.4 parts by mass, the setting time will be too long, which is not conducive to the setting after mixing. If it is too little, the requirement of slow setting to the specified time cannot be achieved. Too much ethylenediaminetetra (methylenephosphonic acid) iron will cause material waste and high cost, while a small amount will not achieve the expected effect.

[0029] In some embodiments, the components in the component B include, by mass, 40-60 parts of desulfurized gypsum, 35-50 parts of fly ash, 5-10 parts of aluminum sulfate, 0.1-2 parts of N-(2-nitrophenyl)ethanolamine and 0.02-0.1 parts of triisopropoxytitanium chloride complex.

[0030] The ratio of desulfurized gypsum to fly ash can be adjusted to each other, but if it exceeds this ratio, more other additives are needed to adjust the performance of the mixed slurry. For example, if the fly ash is too high or too little, the coagulation will slow down after mixing, and more aluminum sulfate or N-(2-nitrophenyl)ethanolamine needs to be added to adjust it. Excessive use of aluminum sulfate will cause waste of materials and high costs, and a small amount will not achieve the expected effect. Excessive use of N-(2-nitrophenyl)ethanolamine will cause waste of materials and high costs, and a small amount will not achieve the expected effect.

[0031] The present invention also provides a method for preparing a coal-based solid waste-based ultra-high water filling material. Figure 1 A flow chart of a method for preparing a coal-based solid waste-based ultra-high water filling material according to some embodiments is exemplarily shown, and the preparation method includes S100-S300.

[0032] S100, mixing component A with water to form a first mixed slurry; in some embodiments, component A is mixed with water in a mass ratio of 1:(5-7) to form the first mixed slurry.

[0033] S200, mixing component B with water to form a second mixed slurry; in some embodiments, component B is mixed with water in a mass ratio of 1:(5-7) to form the second mixed slurry.

[0034] S300, mixing the first mixed slurry and the second mixed slurry to form a coal-based solid waste-based ultra-high water filling material. In some embodiments, the first mixed slurry and the second mixed slurry are mixed in a mass ratio of 1: (0.5-2) to form a coal-based solid waste-based ultra-high water filling material.

[0035] The following examples and comparative examples show that the coal-based solid waste-based ultra-high water filling material in the examples of the present application has good performance. The test materials used in the following examples, unless otherwise specified, were purchased from conventional stores and other channels. The quantitative tests in the following examples were set up for three repeated experiments, and the data are the average or average ± standard deviation of the three repeated experiments.

[0036] Example 1

[0037] Mix 100 parts of sulphoaluminate clinker, 0.2 parts of citric acid and 0.01 parts of ethylenediaminetetra(methylenephosphonic acid) iron, by weight, to obtain component A;

[0038] According to parts by mass, 40 parts of desulfurized gypsum, 50 parts of fly ash, 10 parts of aluminum sulfate, 0.1 parts of N-(2-nitrophenyl)ethanolamine and 0.1 parts of triisopropoxytitanium chloride complex are mixed to obtain component B;

[0039] By weight, 1 part of component A is mixed with 5 parts of water to form a first mixed slurry;

[0040] Based on parts by mass, 1 part of component B is mixed with 5 parts of water to form a second mixed slurry;

[0041] The first mixed slurry and the second mixed slurry are mixed in parts by mass to form a coal-based solid waste-based ultra-high water filling material.

[0042] Example 2

[0043] Mix 100 parts of sulphoaluminate clinker, 0.4 parts of citric acid and 0.02 parts of ethylenediaminetetra(methylenephosphonic acid) iron, by weight, to obtain component A;

[0044] Mix 60 parts of desulfurized gypsum, 35 parts of fly ash, 5 parts of aluminum sulfate, 0.2 parts of N-(2-nitrophenyl)ethanolamine and 0.05 parts of triisopropoxytitanium chloride complex by weight to obtain component B;

[0045] By weight, 1 part of component A is mixed with 5 parts of water to form a first mixed slurry;

[0046] Based on parts by mass, 1 part of component B is mixed with 5 parts of water to form a second mixed slurry;

[0047] The first mixed slurry and the second mixed slurry are mixed in parts by mass to form a coal-based solid waste-based ultra-high water filling material.

[0048] Example 3

[0049] Mix 100 parts of sulphoaluminate clinker, 0.4 parts of citric acid and 0.02 parts of ethylenediaminetetra(methylenephosphonic acid) iron, by weight, to obtain component A;

[0050] Mix 45 parts of desulfurized gypsum, 45 parts of fly ash, 10 parts of aluminum sulfate, 0.2 parts of N-(2-nitrophenyl)ethanolamine and 0.02 parts of triisopropoxytitanium chloride complex by weight to obtain component B;

[0051] By weight, 1 part of component A is mixed with 7 parts of water to form a first mixed slurry;

[0052] Mix 1 part of component B with 7 parts of water by mass to form a second mixed slurry;

[0053] The first mixed slurry and the second mixed slurry are mixed in parts by mass to form a coal-based solid waste-based ultra-high water filling material.

[0054] Example 4

[0055] Mix 100 parts of sulphoaluminate clinker, 0.2 parts of citric acid and 0.02 parts of ethylenediaminetetra(methylenephosphonic acid) iron, by weight, to obtain component A;

[0056] Mix 50 parts of desulfurized gypsum, 45 parts of fly ash, 5 parts of aluminum sulfate, 0.1 parts of N-(2-nitrophenyl)ethanolamine and 0.05 parts of triisopropoxytitanium chloride complex by weight to obtain component B;

[0057] By weight, 1 part of component A is mixed with 7 parts of water to form a first mixed slurry;

[0058] Mix 1 part of component B with 7 parts of water by mass to form a second mixed slurry;

[0059] The first mixed slurry and the second mixed slurry are mixed in parts by mass to form a coal-based solid waste-based ultra-high water filling material.

[0060] Example 5

[0061] Mix 100 parts of sulphoaluminate clinker, 0.2 parts of citric acid and 0.01 parts of ethylenediaminetetra(methylenephosphonic acid) iron, by weight, to obtain component A;

[0062] Mix 50 parts of desulfurized gypsum, 40 parts of fly ash, 10 parts of aluminum sulfate, 0.1 parts of N-(2-nitrophenyl)ethanolamine and 0.05 parts of triisopropoxytitanium chloride complex by weight to obtain component B;

[0063] By weight, 1 part of component A is mixed with 7 parts of water to form a first mixed slurry;

[0064] Mix 1 part of component B with 7 parts of water by mass to form a second mixed slurry;

[0065] The first mixed slurry and the second mixed slurry are mixed in parts by mass to form a coal-based solid waste-based ultra-high water filling material.

[0066] Comparative Example 1

[0067] Mix 100 parts of sulphoaluminate clinker and 0.01 parts of ethylenediaminetetra(methylenephosphonic acid) iron, based on parts by mass, to obtain component A;

[0068] According to parts by mass, 40 parts of desulfurized gypsum, 50 parts of fly ash, 10 parts of aluminum sulfate, 0.1 parts of N-(2-nitrophenyl)ethanolamine and 0.1 parts of triisopropoxytitanium chloride complex are mixed to obtain component B;

[0069] By weight, 1 part of component A is mixed with 5 parts of water to form a first mixed slurry;

[0070] Based on parts by mass, 1 part of component B is mixed with 5 parts of water to form a second mixed slurry;

[0071] The first mixed slurry and the second mixed slurry are mixed in parts by mass to form a coal-based solid waste-based ultra-high water filling material.

[0072] Comparative Example 2

[0073] 100 parts by weight of sulphoaluminate clinker and 0.4 parts by weight of citric acid were mixed to obtain component A;

[0074] Mix 45 parts of desulfurized gypsum, 45 parts of fly ash, 10 parts of aluminum sulfate, 0.2 parts of N-(2-nitrophenyl)ethanolamine and 0.02 parts of triisopropoxytitanium chloride complex by weight to obtain component B;

[0075] By weight, 1 part of component A is mixed with 7 parts of water to form a first mixed slurry;

[0076] Mix 1 part of component B with 7 parts of water by mass to form a second mixed slurry;

[0077] The first mixed slurry and the second mixed slurry are mixed in parts by mass to form a coal-based solid waste-based ultra-high water filling material.

[0078] Comparative Example 3

[0079] 100 parts of sulphoaluminate clinker and 0.2 parts of citric acid were mixed by weight to obtain component A;

[0080] According to parts by mass, 50 parts of desulfurized gypsum, 40 parts of fly ash, 10 parts of aluminum sulfate and 0.05 parts of triisopropoxy titanium chloride complex are mixed to obtain component B;

[0081] By weight, 1 part of component A is mixed with 7 parts of water to form a first mixed slurry;

[0082] Mix 1 part of component B with 7 parts of water by mass to form a second mixed slurry;

[0083] The first mixed slurry and the second mixed slurry are mixed in parts by mass to form a coal-based solid waste-based ultra-high water filling material.

[0084] Comparative Example 4

[0085] Mix 100 parts of sulphoaluminate clinker, 0.2 parts of citric acid and 0.02 parts of ethylenediaminetetra(methylenephosphonic acid) iron, by weight, to obtain component A;

[0086] Mix 50 parts of desulfurized gypsum, 45 parts of fly ash, 0.1 parts of N-(2-nitrophenyl)ethanolamine and 0.05 parts of triisopropoxytitanium chloride complex by weight to obtain component B;

[0087] By weight, 1 part of component A is mixed with 7 parts of water to form a first mixed slurry;

[0088] Mix 1 part of component B with 7 parts of water by mass to form a second mixed slurry;

[0089] The first mixed slurry and the second mixed slurry are mixed in parts by mass to form a coal-based solid waste-based ultra-high water filling material.

[0090] Comparative Example 5

[0091] Mix 100 parts of sulphoaluminate clinker, 0.2 parts of citric acid and 0.02 parts of ethylenediaminetetra(methylenephosphonic acid) iron, by weight, to obtain component A;

[0092] According to parts by mass, 50 parts of desulfurized gypsum, 40 parts of fly ash, 10 parts of aluminum sulfate and 0.1 parts of N-(2-nitrophenyl)ethanolamine are mixed to obtain component B;

[0093] By weight, 1 part of component A is mixed with 7 parts of water to form a first mixed slurry;

[0094] Mix 1 part of component B with 7 parts of water by mass to form a second mixed slurry;

[0095] The first mixed slurry and the second mixed slurry are mixed in parts by mass to form a coal-based solid waste-based ultra-high water filling material.

[0096] The following table describes the components of coal-based solid waste-based ultra-high water filling materials, as well as the test results of setting time and compressive strength, as shown in Table 1:

[0097] Table 1

[0098]

[0099]

[0100] It can be seen from Example 1 and Comparative Example 1 that citric acid plays a retarding role. If citric acid is not added to the system, the slurry coagulation time will be too short, which is not conducive to grouting.

[0101] It can be seen from Example 3 and Comparative Example 2 that ethylenediaminetetra(methylenephosphonic acid) iron can increase the strength by 32%;

[0102] It can be seen from Example 5 and Comparative Example 3 that the simultaneous addition of ethylenediaminetetramethylenephosphonate iron and N-(2-nitrophenyl)ethanolamine can not only allow the setting time to reach a more reasonable range, but also increase the strength by 67%;

[0103] It can be seen from Example 4 and Comparative Example 4 that aluminum sulfate can optimize the slurry setting time and improve the compressive strength;

[0104] It can be seen from Example 5 and Comparative Example 5 that the triisopropoxy titanium chloride complex can promote the synergistic reaction of ethylenediaminetetramethylenephosphonic acid iron and N-(2-nitrophenyl)ethanolamine, improve the system's ore pressure strength and shorten the system's coagulation time.

[0105] In summary, the present invention provides a coal-based solid waste-based ultra-high water filling material and a preparation method thereof. The filling material can improve the utilization rate of coal-based solid waste, reduce material costs, and at the same time improve the stability and strength of the material and enhance environmental adaptability.

[0106] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.

Claims

1. A coal-based solid waste-based ultra-high water filling material, characterized in that: The filling material consists of component A and component B, wherein the component A includes the following components: sulphoaluminate clinker, citric acid and ethylenediaminetetra(methylenephosphonic acid) iron; the component B includes the following components: desulfurized gypsum, fly ash, aluminum sulfate, N-(2-nitrophenyl)ethanolamine and triisopropoxytitanium chloride complex.

2. The filling material according to claim 1, characterized in that: The components in the component A include, by weight: 100 parts of sulphoaluminate clinker, 0.2-0.4 parts of citric acid, and 0.01-0.02 parts of ethylenediaminetetramethylenephosphonic acid iron.

3. The filling material according to claim 1, characterized in that: The components in the second component include, by mass, 40-60 parts of desulfurized gypsum, 35-50 parts of fly ash, 5-10 parts of aluminum sulfate, 0.1-2 parts of N-(2-nitrophenyl)ethanolamine and 0.02-0.1 parts of triisopropoxy titanium chloride complex.

4. The method for preparing the coal-based solid waste-based ultra-high water filling material according to any one of claims 1 to 3, characterized in that: include: Mixing component A with water to form a first mixed slurry; Mixing component B with water to form a second mixed slurry; The first mixed slurry and the second mixed slurry are mixed to form a coal-based solid waste-based ultra-high water filling material.

5. The method according to claim 4, characterized in that Component A is mixed with water in a mass ratio of 1:(5-7) to form a first mixed slurry.

6. The method according to claim 4, characterized in that The second mixed slurry is formed by mixing component B with water in a mass ratio of 1:(5-7).

7. The method according to claim 4, characterized in that The first mixed slurry and the second mixed slurry are mixed in a mass ratio of 1:(0.5-2) to form a coal-based solid waste-based ultra-high water filling material.

Citation Information

Patent Citations

  • Fly ash-based cemented filling material and preparation method thereof

    CN103319123A

  • Novel high-strength high-water-retention coal ash high-water material

    CN107417228A

Cited By

  • Method for preparing underground cemented high-water-expansion filling material from negative carbon all-solid waste and application of underground cemented high-water-expansion filling material

    CN121651840A